Revving up memories: a fun day at the heritage race with friends of archives / Adwina Edward - Edward, Adwina (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
On 24 June 2024, we, students in Diploma of Information Management, UiTM Sarawak Branch, along with our lecturer, Miss Suhaida Halamy, and Madam Nurfaizah Kamarudin, were invited to participate in the Heritage Race, a program organized by Friends of Archives (FOA), Sarawak State Records Repository. We were told to gather at Parking B before 6.30 a.m. because we were going by bus to the State Records Repository. We estimated arriving at the venue at 8 a.m. After arriving, we needed to register as visitors and receive souvenirs. First and foremost, we were given breakfast, which included fried noodles, confectionary, coffee, and tea. At 9:30 a.m., we were given a briefing on the second floor by Mr. Herrie Suliano Mohamad about the tentative activities we would do. Then, we were told to form five groups of five members. Next, the first game we played was weighing the items inside plastic bags; if we succeeded, we could proceed to the next checkpoint. At the second checkpoint, we got a mission to pop the balloons using a blowgun or “sumpit”. At the third checkpoint, we were taught how to preserve maps correctly. If we succeeded, we could move on to the next mission.